Korelasi Secure Attachment Dengan Kemampuan Penyesuaian Diri dan Pengungkapan Bahasa Pada Anak Usia 5 - 6 Tahun - Febru Puji Astuti; Madyawati, Lilis; Putri, Devy Anthonita Eka (PG PAUD Universitas Negeri Surabaya, 2023)
This study aims to determine the correlation of secure attachment with self-adjustment and language disclosure ability in children aged 5-6 years (Group B) in Pertiwi Jurangombo Kindergarten, South Magelang District. The resource method is correlational research of 3 (three) variables. The sampling technique uses purposive sampling with research subjects are 22 children aged 5-6 years (Group B) in Pertiwi Jurangombo Kindergarten, South Magelang District. The methods of data completion using by the open questionnaire of parental-secure attachment, a self-adjustment observation sheet, a language disclosure observation sheet, teacher and parent's interview sheet. The instrument validity test by IBM SPSS Statistics 24 with Pearson Correlation analysis, while the reliability using the Cronbach Alpha coefficient. The data analysis test by using Kendall's Tau-b Correlation Test. The results show a correlation between secure attachment with children's self-adjustment ability and language disclosure. The result of Kendall's Tau-b (T) coefficient is 0.167, that below the limit of 0.5. It shows a weak correlation in which secure attachment contributes 16,7 % to the ability of self-adjustment and language disclosure. On the other hand, 83.3% were influenced by other factors.